Community computing collaboration over global information networks - Ishida, Toru (John Wiley & Sons Ltd, 1998)
Community Computing Collaboration Over Global Information Networks Edited by Toru Ishida Kyoto University, Japan With the success of network software suites, groupware has rapidly acquired a high level of commercial interest. Drawing together the various origins of this technology from distributed computing, communication networks, autonomous agents and multi-agent systems, this book opens an important new avenue of research into global collaboration systems for a wide variety of people. It also makes an interesting case study of human-computer interaction and the role of technologies in virtual communities. This book extends groupware for human communities. Conventional groupware typically supports the cooperative work of formally organized groups of people. The collaboration technologies introduced in this book, unlike conventional groupware, is designed to support the process of organizing people who are willing to share mutual understanding and experiences. Community Computing draws on the combined experience of leading industrial and academic researchers to present the following five stages of social interaction in human communities: